PERAN STIMULASI SENSORIK DAN INTERAKSI IBU DALAM PERKEMBANGAN ANAK USIA DINI: PENDEKATAN HOLISTIK NEUROSAINS DAN PSIKOLOGI ISLAM - Shofia Maghfiroh (Al-ATHFAL: Jurnal Pendidikan Anak, 2026)
This study explores the role of sensory stimulation and mother-child interaction in children aged 0–6 years through a holistic approach integrating neuroscience and Islamic psychology. A qualitative descriptive design was employed, involving 12 mothers as participants. Data were collected through direct observation, semi-structured interviews, activity documentation, observation sheets, and children’s emotional regulation scales. Findings indicate that sensory stimulation, including infant massage, sensory play, storytelling, and motherly interaction such as verbal affection and moral guidance, was performed routinely or frequently by most participants. These activities positively influenced children’s cognitive, social, emotional, and moral development. The analysis links caregiving practices with neuroscience principles emphasizing brain plasticity and neuronal connectivity, and Islamic psychology principles highlighting the development of intellect (akal), heart (qalb), and self (nafs). The study underscores the importance of consistent, warm, and morally guided parenting to foster intelligent, virtuous, and faithful children, and provides practical recommendations for mothers, early childhood educators, and future research with larger and more varied samples.